How to decide : simple tools for making better choices - Duke, Annie, 1965- (Portfolio/Penguin, 2020)
"Through a blend of compelling exercises, illustrations, and stories, the bestselling author of Thinking in Bets will train you to combat your own biases, address your weaknesses, and help you become a better and more confident decision-maker"--